Reduced dose coupled with improved method of neem-coated urea application and foliar sprays of KNO3 enhance cotton yield and fiber parameters under semi-arid climates. (3rd April 2023) - Singh, Kulvir; Mishra, Sudhir Kumar; Rathore, Pankaj; Kumar, Ashok
Abstract: Choice of source, nitrogen rate, and its application method affect cotton productivity. In absence of new recommendations for recently introduced neem-coated urea (NCU) in India, farmers have been applying either similar or above optimal levels of NCU in cotton just like conventional urea. The present study aimed to evaluate the optimum dose and better method of NCU application to improve cotton productivity and profitability under arid climates. A total of eight different treatments were evaluated in a randomized complete block design. Two NCU doses [i.e., 112.5 kg ha −1 (75% of conventional nitrogen [urea] recommendation-CNR) and 150 kg ha −1 (100% of CNR)] were applied using three methods, i.e., (a) band application, (b) spot application, and (c) broadcasting constituted six treatments. In addition, foliar sprays of NCU@1% and KNO3 @2% were also evaluated to study their effect in improving seed cotton yield (SCY) and fiber parameters. These findings elucidated that the spot method of NCU application proved better than the broadcasting and band application method owing to better nitrogen use efficiency (NUE). NCU@ 112.5 kg N ha −1 applied through spot application along with three foliar sprays of KNO3 @2% resulted in similar profitability as that of broadcasting 150 kg NCU ha −1 along with four foliar sprays of KNO3 . Improved physiological parameters like net photosynthesis and chlorophyll coupled with higher NUE played a decisive role for at par SCY despite 25% low nutrient input besides enhanced environment safety. Therefore, under semi-arid climates, 37.5 kg N ha −1 could be saved without compromising cotton productivity.